Social Workers' experiences of forensic practice with victims of child sexual abuse in the City of Cape Town - Pamburayi, Sibonisiwe Pertina (2020)
The prevalent rates of sexual crimes against children in South Africa require forensic social work as a specialised field to assist the criminal justice system to respond effectively to victims' essential needs. This need has led to the employment of social workers in forensic units in the South African Police Services (SAPS) as an investigative aid under detective services to enhance service delivery in forensic practices. The initiative materialised through previous collaboration between the National Department of Social Development (DSD), tertiary institutions and the South African Council of Social Service Professions (SACSSP), to deliberate on strategies to curb the alarming rates of crime, violence and other related social problems in South Africa. Instituting specialised forensic practice was the outcome and it provided context of this study. This study explored social workers' experiences of forensic practice with victims of child sexual abuse in the City of Cape Town. Forensic social work is an emerging field of practice that requires tertiary training for social workers who want to practice forensic social work to acquire specialised knowledge and skills to practice competently. The study objectives involved; ● To explore the challenges faced by social workers providing forensic services to victims of child sexual abuse. ● To discover concerns involved in generalist social workers providing forensic services to victims of child sexual abuse. ● To describe the social workers' decision making in their intervention in providing forensic social work services. ● To explore the levels of knowledge and skills of social workers in forensic practice with sexual abuse cases. The study adopted a qualitative research approach where data was collected using a semistructured interview schedule. The non-probability purposive sampling approach was implemented based on the researcher's judgement of the role players relevant to this study. The sample interviewed for this study comprised of twenty social workers handling child sexual abuse cases from government departments and non-governmental organisations in the City of Cape Town to explore their experiences in handling child sexual abuse victims. The data was analysed using Tesch's (1990) eight steps of data analysis. The findings revealed that collaborative partnerships are at the core of the criminal justice system and networking with relevant role-players and stakeholders allow the handling of these complex cases effectively. However, with the challenging nature and risk involved in forensic social work practice, social workers' attrition rates were high in a field already suffering from the scarcity of human resources. Social workers in forensic practice experience various challenges with child victims, the justice system and collaborations with other role-players. All these challenges are seen as contributing factors to the delay of cases and low conviction rates of sexual offences in South Africa. There is a need therefore to improve collaborations among role players handling child sexual abuse cases for effective service delivery